Damage evolution and failure mechanism induced by microstructural inhomogeneity in bainite steel. (October 2021) - Ren, Chunhua; Zhang, Xiaochuan; Ji, Hongwei; Wang, Huaiwen; Hazra, Sumit.; Zhu, Yuyi; Shollock, Barbara.
Highlights: The error of the experimental method was evaluated using the zero-deformation experiments and 95% confidence intervals. The transmission of strain in the acicular ferrite (AF) area has a significant turn at the granular bainite (GB) boundary. The damage of the AF/GB interface is affected by the loading direction. The crystallographic characteristics of the banded structure were examined. Abstract: This paper presents a study on damage evolution for inhomogeneous structure consisting of acicular ferrite (AF) and granular bainite (GB) in advanced steel. The characteristics of crystal orientation were also analyzed. Firstly, the reliability of the deformed image obtained by repositioning for digital image correlation (DIC) calculation was evaluated using the zero-deformation experiments and 95% confidence interval length. Obtained results show that the influence of rigid body displacement induced by repositioning on the credibility can be ignored, and the accuracy and robustness meet the experimental requirements in this study. Then, tensile tests were carried out in rolling direction (RD) and transverse direction (TD). In RD tensile, the local damage mainly expands continuously inside the adjacent bands. The transmission of strain in the AF area has a significant turn at the GB boundary. Results of TD show that the damage extends along the coarse GB grain boundaries, which is the main reason for the occurrence of microcracks. Moreover, the crystal orientation also displays banded morphology. As the load increases, the fields of AF exhibit the most of increased KAM values at higher stress. The larger size of GB and its single orientation weaken the ability to resist crack propagation. This work helps to fully understand the negative effects of coarse GB morphology on mechanical properties and reveal the damage mechanism.